A gestão da dívida pública no contexto da financeirização da economia brasileira : 1995-2010 - Souza, Maksandro José de (2021)
The economic transformations observed in the Brazilian economy from the 1990s onwards were strongly influenced by neoliberal ideas, summarized in the prescriptions of the Washington Consensus. This set of ideas, recommended by international financial organizations (Inter-American Development Bank – IDB, International Monetary Fund – IMF and World Bank), which emphasize the balance of public accounts as essential to fight inflation, resulted in structural changes in the country's economy, with lasting implications in terms of macroeconomic policies, specifically in the handling of public debt. According to data from the International Monetary Fund (2010) the Brazilian public debt, which was 34% of GDP in 1995 – beginning of the first Fernando Henrique Cardoso (FHC) government – reached 76%, at the end of his second government, in 2002. His successor, President Luiz Inacio Lula da Silva (Lula), completed his second term in 2010 with debt at 63% of GDP. We researched public debt management in the context of the financialization of the Brazilian economy, to seek clarification on how the handling of the Brazilian public debt took place between 1995 and 2010. Thus, we tried to verify whether there was a rupture or continuity in the conduct of debt management in the comparison between the two terms of the FHC government and the two terms of the Lula government. Therefore, it was necessary to assess the role of public debt in the process of capital reproduction in Brazil in the period 1995/2010; to qualify macroeconomic policies, with a monetarist/neoliberal bias, as the main mechanisms for generating and perpetuating public debt during FHC/Lula's governments; and analyze whether the Fiscal Responsibility Law (LRF) submits the Brazilian public budget to the payment of public debt or not. It was intended, therefore, to carry out research that combines the deductive method with the empirical-inductive method. Therefore, it was observed that the public debt constituted the main mechanism of fictitious capital accumulation between the years 1995 to 2010; and that the LRF expressed the hegemony of speculative capital during the FHC/Lula administrations, which imposed the observation that there was no rupture in the public debt regime due to the financialization process observed in the Brazilian economy in the period 1995-2010.